Book Review Essay. Issue 1 (1st July 2021) - Zwart, Inge; Boersma, Susanne; Mucha, Franziska; Kist, Cassandra
Abstract : Care-ful Participation in Museums: A Review of The Museum as a Space of Social Care by Nuala Morse